Autophagy: regulating the seesaw of bone–fat balance - Zhang, Boya; Cui, Jing; Zhang, Xu; Pan, Ziyi; Du, Liuyi; Ye, RongRong; Wen, Linlin; Zhai, Wenhao; Huang, Lei; Li, Daowei; Sun, Hongchen (Frontiers in Cell and Developmental Biology, 2025)
The interrelationship between bone and fat can be described as a seesaw in bone homeostasis, in which both osteogenesis and adipogenesis occur in a delicate balance. Osteoblasts and adipocytes share a common origin and play key roles in osteogenesis and adipogenesis. Bone–fat balance indicates osteogenesis and adipogenesis keeps a balance for concordant distribution of trabecular bone and bone marrow adipose tissue in bone, thereby leading to the balance between bone metabolism and lipid metabolism. Bone–fat balance is crucial for metabolic health. When disrupted by various factors, this balance can lead to several bone-related metabolic diseases and systemic disorders, such as obesity, osteoporosis, and osteoarthritis. Recent research highlights the role of autophagy dysfunction in these metabolic conditions. Restoring autophagic function can help restore metabolic homeostasis and re-establish the bone–fat balance. The current review explores the factors that regulate bone–fat balance, the consequences of imbalance under pathological conditions, and the potential of autophagy modulation as a therapeutic approach. Overall, it can be concluded that targeting autophagy presents a promising strategy for treating metabolic disorders and restoring bone–fat balance.